Research on the Correlation between Plasma BNP and the Condition and Prognosis of Chronic Heart Failure - Ma, Bocong; Zhao, Ming; Guo, Zhihao; Zhao, Zheng (Cellular and Molecular Biology, 2022)
This study aimed to analyze the correlation between the level of brain natriuretic peptide (BNP) and the condition and prognosis of chronic heart failure (CHF). For this purpose, between January 2017 and July 2020, we recruited a total of 120 CHF patients who were treated in Cangzhou Central Hospital into this study, consisting of 40 patients in NYHA II, 40 in NYHA III and 40 in NYHA IV, and simultaneously, 40 subjects with normal heart function were enrolled into the control group. General data were collected from the patients and subjects, and laboratory tests regarding the BNP level, LVEDD and LVEF were carried out. Correlation between plasma level of BNP and the evaluation of condition and prognosis of CHF was also analyzed. For further evaluation, the expression of BNP gene expression was considered in the femoral blood of participants by the Real-time PCR technique. The results showed that comparison over the clinical data of subjects among these groups showed no significant difference (P > 0.05). In the research group, the averages of LVEDD and BNP in plasma were (58.53±3.75) mm and (5089.86±22.39) pg/mL, significantly higher than those in the control group, while the LVEF was (45.66±3.42) %, which was lower than that in the control group (all P < 0.05). For the subgroup comparison, as the NYHA class augmented, patients also had a significant increase in the mortality rate and the difference among subgroups had statistical significance (P < 0.05). Furthermore, with 442 pg/mL as a critical point for BNP, patients in the research group were further divided into the BNP>442 pg/mL group and BNP ≤442pg/mL group, and the statistical analysis revealed that in the BNP>442 pg/mL group, the incidence rate of cardiovascular events, re-hospitalization rate and mortality rate were 53.53%, 14.14% and 7.07%, which were all significantly higher than those in the BNP ≤ 442 pg/mL group (all P < 0.05). Also, BMP gene expression was increased in NYHA II, NYHA III, and NYHA IV groups compared to the control group. However, this increase was statistically significant in the NYHA III group (P <0.05) and in the NYHA IV group (P <0.01) compared to the control group. In conclusion, the level of BNP in plasma can reflect the condition of CHF and is critical to the clinical diagnosis, treatment and prognosis evaluation and evaluation of the BNP gene confirmed the result. Thus, it is worth being promoted in clinical practice.